HUBUNGAN DUKUNGAN KELUARGA DENGAN FUNGSI KOGNITIF PADA LANSIA PENDERITA DIABETES MELLITUS DI DESA CANDIREJO WILAYAH KERJA UPTD PUSKESMAS AIR MOLEK - Efliani, Destria; Yanti, Rifa; Arsi , Desraini; Sumandar, Sumandar; Isni Yuli Lestari Putri, Tengku (Jurnal Ilmu Keperawatan, 2023)
The process of aging experienced by the elderly causes problems related to the development of their lives both in terms of physical, mental, and psychosocial aspects. Family support plays an important role in motivating someone to carry out an activity, such as moral and material support. The high age causes the body to experience the aging process, including the brain. Cognitive function is a problem that elderly diabetics face because it causes a decrease in the process of thinking, perception, attention, and memory.Family support is needed by the elderly who experience changes in their cognitive function. This study aims to determine the relationship between family support and cognitive function in the elderly with diabetes mellitus in Candirejo Village, Air Molek Public Health Center Working Area. The type of research used is quantitative research with a cross-sectional approach. The sample in this study was 50 respondents, with the sampling technique in this study being a non-probability sampling technique with a total sampling type. normal, with as many as 27 respondents (54.0%). There is a relationship between family support and cognitive function in elderly DM with a p value of 0.001. Health workers at the Puskesmas are advised to conduct training and update their knowledge on ways to improve cognitive function in the elderly so that it can be practiced in the community.